Violência de gênero e a constitucionalidade da Lei Maria da Penha (Lei 11.340/2006) - Silva, Manoela Bastos de Almeida e (2010)
This paper supports the defense of the constitutionality of Law 11340/06, more known as Maria da Penha Act, which, besides being in full compliance with the provisions of the 1988 Federal Constitution, was created as a reaction, to fight gender-based violence, as demanded for a long time by women s organizations and International Treaties on women s human rights, such as the Convention on the Elimination of All Forms of Discrimination Against Women, approved by the UNO in 1979 and the Inter-American Convention on the Prevention, Punishment and Eradication of Violence Against Women, of which Brazil is a signatory. Notwithstanding its unequivocal importance in the process of building women s human rights, the Maria da Penha Act, which grants specific protection for women against domestic violence, has been subject of many debates and accused of violating the constitutional principle of equality between men and women, but what we see is that it is no more than a strong resistance to changes discriminatory, deeprooted concepts and practices of society against women and that reinforce the historical hierarchy-based relation between the genders